Vocal repertoire of cooperatively breeding Smooth‐billed Anis. Issue 2 (June 2015) - Grieves, Leanne A.; Logue, David M.; Quinn, James S.
ABSTRACT Calls are functionally diverse signals that mediate behavior in a wide variety of contexts in both passerines and non‐passerines. However, the call‐based acoustic communication systems of non‐passerines have received less attention from investigators than those of passerines. We examined the vocal repertoire of Smooth‐billed Anis (Crotophaga ani), cooperatively breeding cuckoos that live in groups with multiple breeding pairs. We recorded calls from 22 groups over two breeding seasons at the Cabo Rojo National Wildlife Refuge in Puerto Rico. We identified 11 call types and one group vocalization, and used an automated sound measurement program to quantify their acoustic features. Discriminant function analysis (DFA) correctly classified 74.2% of calls based on these features. The vocal repertoire of Smooth‐billed Anis is larger than that reported for the three other species in the subfamily Crotophaginae. Smooth‐billed Anis have at least two alarm calls, two nest‐specific calls, and one nest defense call. We also identified one possible signal of aggressive intent, one possible appeasement signal, and two calls that may communicate identity. The relatively large vocal repertoire of Smooth‐billed Anis and association of distinct call types with different functions and contexts supports the main prediction of the social complexity hypothesis, i.e., species with more complex social systems will have more complex communication systems.